Molecular Characterization of Complete Genome of a Thai Highly Pathogenic Porcine Reproductive and Respiratory Syndrome Virus - Jantafong, Tippawan; Lekcharoensuk, Porntippa (The Thai Journal of Veterinary Medicine, 2014)
Highly pathogenic porcine reproductive and respiratory syndrome virus (HP-PRRSV) causes severe outbreaks in swine leading to serious economic losses in swine industry in Thailand and other countries in Southeast Asia. However, information regarding whole genome characterization of HP-PRRSV isolate in this region is limited. This report describes sequencing and characterizations of the complete nucleotide sequence of a Thai HP-PRRSV isolate, designated HP/Thailand/19500LL/2010 (TH19500LL/10). The complete genomic sequence consists of 189-nt 5¢UTR, 14,982-nt protein-coding region containing 9 ORFs and 150-nt 3¢UTR. In addition, the full-length sequence of Thai HP-PRRSV isolate was compared with that of VR2332 and other HP-PRRSV strains. The genomic sequence of TH19500LL/10 is highly similar to that of BH58/10 isolate, a HP-PRRSV from Laos. Nsp2 of TH19500LL/10 has common 30-amino acid discontinuous deletions. Amino acid comparison showed that GP5 of Thai HP-PRRSV was completely identical to that of other HP-PRRSV including JN-HS, BB0907, 09HEN2 and BH58/10 strains. It shares 98.5% and 89.1% similarity at amino acid level to that of the HP-PRRSV prototype (JXA1) and classical NA prototype (VR-2332), respectively. In addition, in silico functional analysis of structural proteins of TH19500LL/10 was also performed and discussed. This study provides basic knowledge for further studies of HP-PRRSV related to molecular mechanisms of viral infection and pathogenesis.